Identification of research priorities of radiography science: A modified Delphi study in Europe - Törnroos Sanna; Pasanen Miko; Leino-Kilpi Helena; Metsälä Eija (WILEY, 2025)
Radiography science is a new discipline among health sciences. It is a discipline that investigates phenomena in medical imaging, radiation therapy, and nuclear medicine. It has merged from the need to provide research evidence to support these services. The domain of the discipline needs clarification and more research should be focused on its paradigmatic issues. Radiography research priorities have been previously charted on a national level in different countries but the viewpoint has been that of the needs of the profession, not of the discipline. This study aimed to identify the priorities of the discipline. The method chosen was a modified version of the Delphi technique with two rounds. The expert panel consisted of 24 European radiography researchers with long professional experience. This study shows that the research priorities in radiography science are related to the phenomena of radiographers' profession, clinical practices, and the safe and high-quality use of radiation and technology for medical imaging, radiotherapy, and nuclear medicine. Identifying these priorities can help focus research onto most important topics and clarify disciplinary perspective.